Propriedades mecânicas e eletrônicas de estruturas híbridas com deformação axial - Oliveira, Igor Santos (2022)
In this work, first-principles methods were used, using density functional theory to investigate the mechanical and electronic properties of BCN hybrid monolayers. The Young’s modulus was obtained for the different structures studied, as well as the electronic structure. From the results for Young’s modulus, we can see that its value depends on the concentration of BN in the carbon matrix, as well as the concentration of carbon in the BN matrix. The structures have been shown to withstand a high strain value (between 15% and 22%) before fracture, which starts at the weakest C-B and C-N bonds located on the boundaries between graphene and h-BN. Regarding the electronic properties, the results showed a variation in the energy gap depending on the structure composition, which covers a wide range of values ranging from 0.8 eV to 3.5 eV. However, deformation weakly alters the energy gap, showing that there is a greater dependence on concentration than on deformation. The combination of atomic scale thickness, high tensile strength and adjustable energy gap suggests that BCN hybrid structures are materials with potential use in electronic devices.